The Study of Proverbs from a Linguocognitive Perspective: Analysis and Interpretation - Nazarov , Qobilbek (The Lingua Spectrum, 2025)
This article provides an in-depth analysis of the linguocognitive features of Uzbek folk proverbs, examining their role in reflecting the worldview, culture, and life experiences of the people. Proverbs serve as important linguistic units that express the spiritual values, ways of thinking, and beliefs of the nation, functioning as a fundamental part of the socio-cultural knowledge system passed down from generation to generation. The study analyzes the concepts embedded in proverbs based on a linguocognitive approach and identifies their place within the system of knowledge formed in human cognition. Particular attention is paid to revealing the deep semantic layers of information conveyed through proverbs and explaining the images and perceptions they form in the minds of the people. The article also explores the mechanisms through which national mentality and social experience are transmitted via proverbs. Relying on linguistic and cognitive analysis methods, the research aims to highlight the semantic structure, conceptual foundations, and cultural significance of Uzbek folk proverbs